2023
DOI: 10.1002/advs.202206325
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Structure Formation in Highly Oriented Triple Cation Perovskite Films

Abstract: Metal halide perovskites are an emerging class of crystalline semiconductors of great interest for application in optoelectronics. Their properties are dictated not only by their composition, but also by their crystalline structure and microstructure. While significant efforts are dedicated to the development of strategies for microstructural control, significantly less is known about the processes that govern the formation of their crystalline structure in thin films, in particular in the context of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…These three factors were empirically found to influence the quality of the perovskite films, and consequently the performance of perovskite solar cells. 57,67,72 Importantly, a study by Taylor et al demonstrated that these factors have significant implications for the choice of optimal processing conditions of the layers. 72 There, the 14 investigated antisolvents were categorised into type I, type II and type III based on the optimal antisolvent application rate that led to high solar cell performance (Fig.…”
Section: Antisolvent Categorisation and Impact On Processing Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…These three factors were empirically found to influence the quality of the perovskite films, and consequently the performance of perovskite solar cells. 57,67,72 Importantly, a study by Taylor et al demonstrated that these factors have significant implications for the choice of optimal processing conditions of the layers. 72 There, the 14 investigated antisolvents were categorised into type I, type II and type III based on the optimal antisolvent application rate that led to high solar cell performance (Fig.…”
Section: Antisolvent Categorisation and Impact On Processing Conditionsmentioning
confidence: 99%
“…For example, we recently demonstrated that the occurrence of a templating intermediate can influence grain orientation and consequently performance and stability but varies strongly based on the antisolvent used. 67 …”
Section: Solvent-engineering In Metal Halide Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations